USING SONG TO IMPROVE VOCABULARY MASTERY FOR ELEMENTARY SCHOOL - Ramadini, Amelia; Halimah, Siti (PROJECT (Professional Journal of English Education), 2019)
The purpose of this reseach is to know how the use song to improve the students’ vocabulary mastery in  learning English for elementary school students. The population of this research is SD Lebak Gede it consist thirty student. To analyzed the data the research using SPSS versi 17.0. The test of normality is feris step to know the data is normality distributed. Kolmogorov-smirnov test was used in this research, it can be seen the significant of Kolmogorov-smirnov from pretest was 0.36 and posttest was 0.30 is higher than 0.50. It means that the data is normality distributed. The t-observed of pretest is 21.921 and t-observed of posttest was 56.550. The degree of freedom (df) 29 is 1.691. It means that t-observed of this research is higher than the t-table. The significance (2-tailed) of the data was 0.000 is lower than 0.05. It menas that the data of pretest and posttest is significant. Minimum score pretest was 30 and the maximum score pretest was 80, and the minimum score of posttest was 70 and maximum of posttest was 100. The mean of pretest score 54.60 and the mean of posttest was 81.07. The standard deviation of pretest was 13.642 and standar deviation of posttest was 7.852. It means, the data was improvement. Found that teaching vocabulary mastery using song for elementary school is effective. Keywords:  Teaching Vocabulary, Using Song